PRODUCT QUALITY CONTROL ANALYSIS BY USING STATISTICAL PROCESSING CONTROL ON PRINTING SAKILA JEMBER - Ahmad Sauqi; Helmi Agus Salim; Saiful Amin (STIE Mandala Jember, 2022)
The pandemic has made many businesses out of business, one of the affected business activitiesis Sakila's printing business. Initial surveys show an average of 4.46% of production damage.The direction of this research is to control quality with statistical aids in the form of SPC. Theresults showed that this printer experienced various deviations, as evidenced by the p chart valuewhich was still outside the control limit. The graphic map showed there were 17 points outsidethe control limit. The total damage from 6 product items for a month amounted to 4543 from atotal production of 70,647. Sequentially, the worst damage was in the opaque damage 2740, thedamage was not in accordance with the layout 1008 and the damage due to being cut was 795.The factors causing the damage were workers, production machines, raw materials, workmethods and the work environment.